Primary School Students’ Discipline through Scouting - Putra, M. Jaya Adi; Hermaya, Vera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The research aims to determine the discipline of students through scouting. This type of research is quantitative research with a correlational approach. The population used in this study were 81 Scouting students. Sampling using a saturated sampling technique. The instruments used in this study were scouting questionnaires. Data were analyzed using statistical analysis techniques, namely using the correlation test, significance test and test coefficient of determination. Based on the results of data processing it can be seen that student discipline is in a fairly good category with a percentage of 66.67% and scouting is in a fairly good category with a percentage of 66.67%. Based on the results of testing the hypothesis it is known that the discipline of students through scouting is 0.398. Based on the results of significant tests obtained t-test value of 3.853. Then based on the test results of the determinant coefficient there is the influence of the contribution among variables at 15.8%. This means that there is a scouting contribution of 15.8% towards student discipline, while 84.2% is influenced by other factors not examined in this study.